Performance Evaluation of Redundant Parallel Manipulators Assimilating Motion/Force Transmissibility - Fugui Xie; Xin-Jun Liu; Jinsong Wang (International Journal of Advanced Robotic Systems, 2011)
Performance evaluation is one of the most important issues in the field of parallel kinematic manipulators (PKMs). As a very important class of PKMs, the redundant PKMs have been studied intensively. However, the performance evaluation of this type of PKMs is still unresolved and a challenging endeavor. In this paper, indices that assimilate motion/force transmissibility are proposed to evaluate the performance of redundant PKMs. To illustrate the application of these indices, three PKMs with different kinds of redundancies are taken as examples, and performance atlases are plotted based on the definitions of the indices. Transmissibility comparisons between redundant PKMs and the corresponding non‐redundant ones are carried out. To determine the inverse solutions of the PKMs with kinematic redundancy, an optimization strategy is presented, and the rationality of this method is demonstrated. The indices introduced here can be applied to the performance evaluation of redundant parallel manipulators.